MULTICULTURALISM IN KAZAKHSTAN - KADYRALIYEVA, A.; ZHOLDUBAEVA, A.; MUKHANBET, A; OMIRBEKOVA, A; SAPAROVA, Y.; DARIBAEVA, R. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT Unlike the European Union, several Western countries, multiculturalism is still relevant as it allows to tackle effectively the problem of a multicultural society. Also, the leaders of the CIS countries have repeatedly announced their commitment to this ideology. In this paper, based on the experience at Queen’s University in Canada, the index of the policy of multiculturalism for the first time was calculated for Kazakhstan, the largest country in the Central Asian region. The policy index of multiculturalism in Kazakhstan allows measuring the level of the democratic system of state policy relating to national minorities and migration. RESUMEN A diferencia de la Unión Europea, varios países occidentales, el multiculturalismo sigue siendo relevante, ya que permite abordar eficazmente el problema de una sociedad multicultural. Además, los líderes de los países de la CEI han anunciado repetidamente su compromiso con esta ideología. En este documento, basado en la experiencia de la Queen’s University en Canadá, se calculó por primera vez el índice de la política de multiculturalismo para Kazajstán, el país más grande de la región de Asia Central. El índice de políticas de multiculturalismo en Kazajstán permite medir el nivel del sistema democrático de políticas estatales relacionadas con las minorías nacionales y la migración.